Vocabulary from Latina in the publicistic of M. Hrushevsky (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article is devoted to investigation of lexical borrowings from Latina in the publicistic of M. Hrushevsky; the analysis of semantic composition and functional features of latinisms are made there, their stylistic status in the modern literary language is also determined in the article.
Keywords: borrowing; latinism; term; determinologisation; substandard